2009
DOI: 10.1038/emboj.2009.6
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of raft lipids in T-cell plasma membrane domains engaged in TCR signalling

Abstract: Activating stimuli for T lymphocytes are transmitted through plasma membrane domains that form at T-cell antigen receptor (TCR) signalling foci. Here, we determined the molecular lipid composition of immunoisolated TCR activation domains. We observed that they accumulate cholesterol, sphingomyelin and saturated phosphatidylcholine species as compared with control plasma membrane fragments. This provides, for the first time, direct evidence that TCR activation domains comprise a distinct molecular lipid composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
220
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 256 publications
(243 citation statements)
references
References 51 publications
16
220
4
Order By: Relevance
“…Along the same lines, increased saturation of the hydrocarbon chains would increase interaction with Chol (35) and longer fatty acids could promote interleaflet coupling of a raft assembly (36). Consistent with earlier raft preparations, we find increased levels of 37,38). However, only isolating the apical membrane from polarized MDCK cells will tell us whether the lipids that characterize the polarized cells are indeed enriched there, however.…”
Section: Discussionsupporting
confidence: 75%
“…Along the same lines, increased saturation of the hydrocarbon chains would increase interaction with Chol (35) and longer fatty acids could promote interleaflet coupling of a raft assembly (36). Consistent with earlier raft preparations, we find increased levels of 37,38). However, only isolating the apical membrane from polarized MDCK cells will tell us whether the lipids that characterize the polarized cells are indeed enriched there, however.…”
Section: Discussionsupporting
confidence: 75%
“…That the T cell plasma membrane of fixed cells that are in contact with beads coated with anti--CD3 antibody is more ordered than the rest of the T cells plasma membrane, has been demonstrated by studying laurdan generalised polarisation [16,17]. In a very recent study by the same group, it was demonstrated that lipids expected to form lipid rafts like cholesterol, sphingomyelin and PC with saturated acyl chains accumulate where T cells interact with beads covered in antibodies against the T cell receptor [21]. Intriguingly, accumulation of the same lipids was seen also when T cells interacted with beads coated with antibodies against the non lipid raft marker the TfR.…”
Section: Discussionmentioning
confidence: 95%
“…Stabilisation or formation of large lipid rafts has been demonstrated to trigger all these pathways, since they can be activated by the aggregation of the ganglioside GM1 using cholera toxin B subunit (CT--B) and anti--cholera toxin [19,20]. This links reorganisation of lipids to T cell signaling, as does a recent study where it was shown that raft lipids, like cholesterol and sphingomyelin, accumulate where beads coated with TCR activating antibodies interact with a T cell [21]. However, the role of lipid rafts in TCR signalling is continuously being questioned [22--24].…”
Section: Introductionmentioning
confidence: 83%
“…Future study should focus on how the MARVEL domain-lipid interaction is used for diverse cellular tasks (Anton et al, 2008;Zech et al, 2009).…”
Section: Mechanism Of Mal and The Marvel Domainmentioning
confidence: 99%